Mudanças no trabalho dos servidores técnico-administrativos em educação: o caso da Universidade Federal de Goiás - Machado, Ana Cristina Pinehiro (2024)
This research addresses the transformations in the work of technical-administrative servers in education (TAE), based on the case of the Federal University of Goiás (UFG). The main objective of the study was to understand, from the workers' perspective, the reconfiguration of TAE work since 1995, considering the neoliberal context and structural changes in the realms of work, the state, and higher education globally. TAE servers constitute the staff of Brazilian Federal Institutions of Higher Education (Ifes) and currently form the largest category of public servants in the Executive branch, with over 130 thousand active workers, essential in the dynamics of federal higher education. Engaged in internal and external disputes and conflicts within the category, facing resource scarcity, striving for the full establishment of their career, navigating contradictions, and daily tensions in a large university, TAE servers historically bear the crises affecting Brazilian public higher education, diminishing in quantity but growing in qualification. This sector has undergone significant challenges and profound transformations in Brazil, especially after 1995, with the State reform and the implementation of the managerial model of public administration, gradually subjecting it to neoliberal logic and market standards. It's a case study covering the period between 1995, when Fernando Henrique Cardoso (FHC) took office as Brazil's president and intensified the implementation of neoliberal measures, and 2018, at the end of Michel Temer's government (2016-2018). Theoretical support for the study comes from critical authors on neoliberalism – Dardot and Laval (2016, 2019), Harvey (2014), Miranda (2020, 2023); labor – Antunes (2014, 2018, 2020), Rifkin (2004), Pochmann (2011, 2016, 2022); and higher education in Brazil – Dourado (2017, 2019), Dourado, Moraes (2020, 2021), Oliveira (2000), Oliveira and Dourado (2017), Oliveira and Lima (2019). The empirical research took place in 2023, involving 2,205 permanent active UFG TAE servers through interviews and questionnaire applications. The results reveal a workforce agitated by the constant and increasingly aggressive movement of neoliberal rationality, encroaching upon public power, processes, and work relations. TAE servers identify the major drivers of changes in their professional context as: new technologies, transforming the TAE way of working; the lack of appreciation for the category's role in the functioning of Ifes; and, not least significant, the renewal of the category itself, as new-profile servers join, contributing to many other changes.